The Māori and Ancient near Eastern Pantheons in the Context of Genesis 1 in te reo Māori - Drake, Lyndon (Religions, 2024)
The recent test translation of Te Paipera Tapu (the Bible in the Māori language) has aroused considerable debate for its use in Genesis 1 of the names of atua Māori (Māori divine beings). These names of atua have been used instead of names of features of the natural world, which stands in contrast to the use of other kupu Māori (Māori words) in the earlier translation and its revisions. In this paper, I outline relevant members of the Māori pantheon and of some ancient Near Eastern pantheons, which are not identical. I then discuss the Hebrew text of Genesis 1 in its ancient literary context, making proposals about the use of the names of atua Māori in translations.